Independent risk factors of 30‐day outcomes in 1264 patients with peptic ulcer bleeding in the USA: large ulcers do worse. Issue 10 (22nd March 2016) - Camus, M.; Jensen, D. M.; Kovacs, T. O.; Jensen, M. E.; Markovic, D.; Gornbein, J.
Summary: Background: Predictors of worse outcomes (rebleeding, surgery and death) of peptic ulcer bleeds (PUBs) are essential indicators because of significant morbidity and mortality rates of PUBs. However those have been infrequently reported since changes in medical therapy (PPI, proton pump inhibitors) and application of newer endoscopic haemostatic technique. Aims: To determine: (i) independent risk factors for 30‐day rebleeding, surgery, and death and (ii) whether ulcer size is an independent predictor of major outcomes in patients with severe PUB after successful endoscopic haemostasis and treatment with optimal medical (high dose IV PPI) vs. prior treatment (high dose IV histamine 2 antagonists – H2RAs). Methods: A large prospectively followed population of patients hospitalised with severe PUBs between 1993 and 2011 at two US tertiary care academic medical centres, stratified by stigmata of recent haemorrhage (SRH) was studied. Using multivariable logistic regression analyses, independent risk factors for each outcome (rebleeding, surgery and death) up to 30 days were analysed. Effects for medical treatment (H2RA patients 1993–2005 vs. PPIs 2006–2011) were also analysed. Results: A total of 1264 patients were included. For ulcers ≥10 mm, the odds of 30‐day rebleeding increased 6% per each 10% increase in ulcer size (OR 1.06, 95% CI 1.02–1.10, P = 0.0053). Other risk factors for 30‐day rebleeding were major SRH, in‐patient start of bleeding, and prior GI bleeding. Major SRH and ulcer size≥10 mm were predictors of 30‐day surgery. Risk factors for 30‐day death were major SRH, in‐patient bleeding, and any initial platelet transfusion or fresh frozen plasma transfusion ≥2 units. Among patients with major SRH and out‐patient start of bleeding, larger ulcer size was also a risk factor for death (OR 1.08 per 10% increase in ulcer size, 95% CI 1.02–1.14, P = 0.0095). Ulcer size was a significant independent variable for both time periods. Conclusions: Ulcer size is a risk factor for worse outcomes after PUB and should be carefully recorded at initial endoscopy to improve patient triage and management.